The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00429-019-01830-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of copper levels in the hair with gray matter volume, mean diffusivity, and cognitive functions

Abstract: Although copper plays a critical role in normal brain functions and development, it is known that excess copper causes toxicity. Here we investigated the associations of copper levels in the hair with regional gray matter volume (rGMV), mean diffusivity (MD), and cognitive differences in a study cohort of 924 healthy young adults. Our findings showed that high copper levels were associated mostly with low cognitive abilities (low scores on the intelligence test consisting of complex speed tasks, involving reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…Self-reported height, and BMI are included as covariates to exclude confounding effects of these as these variables often correlate with body mineral levels (in the case of zinc, after correcting the effects of age and sex, BMI was significantly negatively correlated with hair zinc levels, p = 0.002, although, height was not). And this is in accordance with our studies 17 , 60 .…”
Section: Methodssupporting
confidence: 94%
“…Self-reported height, and BMI are included as covariates to exclude confounding effects of these as these variables often correlate with body mineral levels (in the case of zinc, after correcting the effects of age and sex, BMI was significantly negatively correlated with hair zinc levels, p = 0.002, although, height was not). And this is in accordance with our studies 17 , 60 .…”
Section: Methodssupporting
confidence: 94%
“…High copper plasma concentrations have been associated with loss of cognitive performance in normal women (Table 1) [235], and a poorer working memory and attention in children [236] and adolescents [237] (Table 1). A recent study found that copper in hair correlates with low cognitive abilities, high regional gray matter volume over widespread areas of the brain, and larger indices of low density in brain tissues (Table 1) [238]. As a whole, these studies indicate that elevated noncp-Cu is associated with loss of cognitive performance.…”
Section: Clinical Evidence: Copper Dyshomeostasis In Admentioning
confidence: 70%
“…In addition, subjects were instructed to avoid alcohol the night before the assessment. The descriptions in this subsection were mostly reproduced from another study of ours from the same project using the exactly same methods 45 .…”
Section: Methodsmentioning
confidence: 99%
“…These additional analyses, including that of hair perm history as a covariate, did not substantially affect the strength of significant associations in the present study. The descriptions in this subsection were mostly reproduced from our previous study 45 , 47 , which used the similar methods.…”
Section: Methodsmentioning
confidence: 99%